Die Yoruba-Städte in Südwest-Nigerien: Ein Bericht über den Stand der Forschung - Hoffmann-Burchardi, Helmut (ERDKUNDE, 1964)
One of the most striking examples of indigenous African urbanization is afforded by the Yoruba in the Western Region of Nigeria, who in 1952 numbered 5,046,799 people with a long, pre-colonial urban tradition. Nearly 50% of their population live in large, dense, com pact and permanent settlements of 5,000 people or more. The census of 1952 gave the number of Yoruba towns as 120, 12 of which had a population exceeding 40,000, while another 20 reached a figure of some 20,000. In recent times the Yoruba have increasingly caught the attention of English, American and Nigerian scholars (sociologists, anthropologists, historians, archaeologists, geographers), Bascom having been the first to undertake extensive field work among them (1937/38 and 1950/51) and to emphasize the unique degree of their urbanization comparable to European and American standards. Unlike most other African towns those of the Yoruba are based on the traditional African lineage structure, their inhabitants showing a high degree of social homogeneity, stability and continuity. Another distinctive feature of the Yoruba town is that, inspite of a comparatively high degree of trade and craft specialization, the majority of people (approximately 70 %) are still engaged in agriculture, which, however, under modern conditions and the impact of cocoa farming is rapidly changing from a subsistence to a market economy. It is mainly for these two reasons that Yoruba towns lack the basic conditions and functions characteristic of European and American towns. The outward appearance (= morphology) as well as the social structure of these towns, which in part still follow long-established African village patterns, clearly prove this difference. We are therefore faced with a problem of definition, the question being, if the term town in the strict sense of the word can be applied to the nucleated settlements of the Yoruba at all. Most authorities would agree that, within their cultural context, they may well be called towns even in pre-colonial days, because, for one thing, their inhabitants were economically interdependent and engaged in various economic activities, and they were also socially stratified, politically unified and had established an elaborate hierarchical system of administration and government which was balanced between the old egalitarian and gerontocratic principles of African village communities and the autocratic, centralizing tendencies of various town kings, who acknowledged the Alafin of the Oyo Empire established in the Guinea savannah as their supreme suzerain up to the 19th century.